EFL Learners' Memory Strategies in Vocabulary Learning: A Psycholinguistic Perspective - Nurfitriyani, Aisyah; Isnaini Cahyaningsih; Nextarinda Anora; Putri Febriana Rahmawati; Roihanatul Istianah (Studies in Language, Education, and Culture (SeLEC), 2025)
Vocabulary plays an essential role in supporting comprehension of academic texts and the development of critical thinking among EFL learners. However, many learners continue to struggle with limited vocabulary mastery. This study aimed to examine the memory strategies used by EFL learners in vocabulary acquisition from a psycholinguistic perspective. The research involved 36 sixth-semester students of the English Education Study Program at UIN Raden Mas Said Surakarta. A mixed-method design was implemented, using interviews to explore learners’ memory strategies and questionnaires to identify their tendencies in vocabulary memorization. The findings indicate that learners employ varied memory strategies that influence the effectiveness of vocabulary retention. These results highlight the need for instructional practices that integrate memory-based approaches in vocabulary teaching. The study contributes to psycholinguistic research by providing empirical evidence on how memory strategies shape vocabulary learning among EFL learners.